Effect of dexmedetomidine on postoperative cognitive dysfunction in elderly patients after general anaesthesia: A meta-analysis. (December 2016) - Zhou, Chengmao; Zhu, Yu; Liu, Zhen; Ruan, Lin
Objective: We undertook a meta-analysis to investigate the effect of dexmedetomidine on postoperative cognitive dysfunction (POCD). Methods: We searched PubMed, EMBASE, the Cochrane Library, CNKI and Google Scholar to find randomized controlled trials (RCTs) of the influence of dexmedetomidine on POCD in elderly adults who had undergone general anaesthesia. Two researchers independently screened the literature, extracted data, and evaluated methodologic quality against inclusion and exclusion criteria. We used RevMan 5.2 to undertake our meta-analysis. Results: Thirteen RCTs were included. Compared with controls, dexmedetomidine: 1) significantly reduced the incidence of POCD (relative risk = 0.59, 95% confidence interval [CI] 0.45–2.95) and improved Mini-Mental State Examination (MMSE) score (mean difference, MD = 1.74, 95% CI 0.43–3.05) on the first postoperative day; and 2) reduced the incidence of POCD after the first postoperative day (MD = 2.73, 95% CI 1.33–4.12). Conclusion: Dexmedetomidine reduces the incidence of POCD and improves postoperative MMSE score.